Medical technology assessment directory : a pilot reference to organizations, assessments, and information resources - Goodman, Clifford (National Academy Press, 1988)
Intended as introductory work "that organizes recent and current assessment information from a broad though not comprehensive selection of assessment programs and related activities." Includes mainstream information sources, as well as pertinent gray or "fugitive" literature. Arranged under program profiles, thesaurus and citations by technology, information and data resources, and organizational resources. Organizations index. Miscellaneous appendixes.